Commonality in Liquidity Across International Borders: Evidence from Futures Markets. Issue 8 (3rd April 2014) - Frino, Alex; Mollica, Vito; Zhou, Zeyang
<x xml:space="preserve">Abstract</x> This study examines commonality in liquidity for stock index futures markets. We report strong evidence of commonality in global liquidity for nine index futures contracts over a 10‐year time period extending October 2002 to September 2012. Our results are robust to expiry effects and tests for liquidity commonality based on a market model and principal component method. We investigate the variation in global liquidity commonality through time and document that liquidity commonality is higher in significance and more pervasive in recent years. © 2014 Wiley Periodicals, Inc. Jrl Fut Mark 34:807–818, 2014